Research on Deep Cooperation and Collaborative Development Between China and Indonesia Cross-Border E-commerce Based on Silk Road E-Commerce: “丝路电商”背景下中国与印尼跨境电子商务深度合作与协同发展研究 - Li, Zhang; Yalin, Yang; Jiarui, Jiang; Guangxian, Ni (Mandarinable: Journal of Chinese Studies, 2000)
With the rapid development of "Silk Road E-commerce", the cross-border e-commerce cooperation between China and countries along the "Belt and Road" is gradually deepening. As a major e-commerce country and the initiator of "Silk Road E-Commerce", China has rich experience and a good material foundation. As the largest economy of ASEAN and one of the partner countries of "Silk Road E-Commerce", Indonesia has a broad market and a huge consumer base. The cross-border e-commerce sector between China and Indonesia has shown strong complementary and synergistic development capabilities. This paper first analyzes the basic situation of "Silk Road E-commerce", followed by an in-depth analysis of the current situation, development pain points and cooperation space of cross-border e-commerce in China and Indonesia, and puts forward six suggestions for the development of cross-border e-commerce in China and Indonesia, which provide strong academic support for scholars in this field.